In-Situ Observation of Co-Ce Coated Metallic Interconnect Oxidation Combined with High-Resolution Post Exposure Analysis. (30th May 2017) - Poitel, Stéphane; Wang, Zhujun; Willinger, Marc; Van herle, Jan; Hébert, Cécile
Abstract : Oxidation of Sanergy SSHT steel with Ce-Co coating, used as interconnect material, was observed in-situ in a modified environmental scanning electron microscope (ESEM) at nominal temperature between 800°C and 900°C under 33Pa of oxygen, for different durations (up to 60h). After these in-situ observations, lamellas of the observed target areas were prepared using a focused ion beam (FIB). This allowed the evaluation in the cross section of the final composition of the oxidation layers of the steel by scanning transmission electron microscopy (STEM) and energy dispersive x-ray analysis (EDX), of the same zone observed directly on the surface by ESEM. Results show the diffusion of manganese and iron towards the cobalt coating. Underneath, chromia scale forms. Under the applied conditions, the very thin cerium layer does not prevent the diffusion of other elements from the steel. Niobium (with silicium) and titanium form oxidized precipitates in the steel just below the chromia scale.